2014
DOI: 10.1089/ham.2013.1150
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent High Altitude Exposure, Occupation, and Body Mass Index in Workers of Mining Industry

Abstract: The obesity and overweight rates in population exposed to chronic intermittent exposure to high altitudes are not well studied. The aim of the retrospective study was to evaluate whether there are differences in body mass index in different occupation groups working in intermittent shifts at mining industry at high altitude: 3800-4500 meters above sea level. Our study demonstrated that obesity and overweight are common in workers of high altitude mining industry exposed to chronic intermittent hypoxia. The obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
3
12
0
3
Order By: Relevance
“…The first concept is that this population seems to share distinctive and unique features. In fact, there is a remarkable proportion of overweight and sedentarism, as has been previously reported (Esenamanova et al, 2014 ). Smoking habit proportion is similar to Chilean prevalence.…”
Section: Discussionsupporting
confidence: 77%
“…The first concept is that this population seems to share distinctive and unique features. In fact, there is a remarkable proportion of overweight and sedentarism, as has been previously reported (Esenamanova et al, 2014 ). Smoking habit proportion is similar to Chilean prevalence.…”
Section: Discussionsupporting
confidence: 77%
“…A pesar de estos hallazgos, la información antropométrica recolectada en nuestro estudio es opuesta a lo citado en la literatura, en donde se expone que la exposición a la altitud bajo un modelo de exposición aguda genera una baja de peso, debido a un balance energético negativo, producto principalmente al aumento de la tasa metabólica basal, y la supresión del apetito 8 . Es más, estudios han demostrado que la permanencia en un ambiente hipóxico hipobárico podría incluso ser utilizado como tratamiento para la obesidad, debido a los motivos antes señalados 8,28 .…”
Section: Resultsunclassified
“…Cuando este tipo de sistema laboral y exposición ambiental ocurre en un periodo intermitente, se habla de un modelo de exposición a un ambiente hipóxico hipobárico crónico e intermitente (HHCI), el cual es conocido como "El modelo chileno" 2,3,4,5,6 . Este tipo de exposición ocasiona una serie de cambios fisiológicos en el ser humano, los que pueden desencadenar trastornos a corto y largo plazo en altitudes por sobre los 3500 m 7,8 . Estas, se pueden manifestar como cefaleas, alteraciones en la calidad del sueño, mal agudo de montaña, alteraciones neurológicas, cardiopulmonares, entre otras.…”
Section: Introductionunclassified
“…A recent study examining shifts over 15 days from the Kyrgyz at altitudes of 3,800-4,500 m demonstrated that obesity and overweight are common in workers in the high-altitude mining industry exposed to CIH [52]. Similarly, a high prevalence of increased BMIs was described in a previous study of soldiers working at 3,550 m (shifts, 5 × 2 days) [11] and in 76 young recruits during a follow-up at the same altitude [53].…”
Section: Obesity and Chronic Intermittent Exposure To High-altitude Hmentioning
confidence: 99%